The Princeton Handbook of Poetic Terms - Preminger, Alex (Book collections on Project MUSE., 2014)
This compact volume makes available a selection of 402 entries from the widely praised Princeton Encyclopedia of Poetry and Poetics, with emphasis on prosodic and poetic terms likely to be encountered in many different areas of literary study. The book includes detailed discussions of poetic forms, prosody, rhetoric, genre, and topics such as theories of poetry and the relationship of linguistics to poetry Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the dis.